Peran Keterampilan Bertanya Guru Terhadap Perkembangan Kognitif Anak Usia Dini - Nurainun Nurainun; Mila Rizky; Nur Halimah; Kholidah Nur (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2025)
Questioning skills are skills that teachers must develop in the teaching and learning process. The aim of this research is to illustrate how teachers' questioning skills play an important role in stimulating the cognitive development of early childhood. This research method uses descriptive qualitative research which collects data through interviews, documentation and observation. The subjects of this research were young children who received institutional education. In fact, teachers' questioning skills have been proven to have a significant impact on the cognitive development of young children. Teachers' questioning skills can increase children's curiosity and improve children's memory, imagination and creativity in finding answers in the teaching and learning process. It can be concluded that teachers' questioning skills play a very important role in improving children's cognitive development. Because through these questions children can continue their thinking processes, obtain new information and expand their knowledge.